1978
DOI: 10.1002/ajpa.1330480102
|View full text |Cite
|
Sign up to set email alerts
|

Incisal bite force direction in humans and the functional significance of mammalian mandibular translation

Abstract: Incisal bite force direction was recorded and analyzed in ten human subjects using a specially designed force transducer. In all ten subjects the maxillary incisal bite force was vertically and anteriorly directed both during static biting and during biting associated with simultaneous mandibular translation and rotation. Since the resultant muscle force could not have been equal and opposite to the mandibular bite force, the mandibular condyles must have been loaded. These data demonstrate that the mandible a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
1
1

Year Published

1978
1978
2005
2005

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(30 citation statements)
references
References 14 publications
1
27
1
1
Order By: Relevance
“…The asymmetry of retractive and protrusive shear forces predicted by this model appears to be a contrary result to that reported by Koolstra et al (1988) and thus might tend to agree with Hylander's (1978) finding for incisal bite force direction. Greater protrusive shear would be the result expected from the anatomy of the masticatory muscles, since the muscle mass capable of exerting a retractive pull on the mandible is much less than that which can exert a protrusive pull.…”
Section: Discussioncontrasting
confidence: 61%
“…The asymmetry of retractive and protrusive shear forces predicted by this model appears to be a contrary result to that reported by Koolstra et al (1988) and thus might tend to agree with Hylander's (1978) finding for incisal bite force direction. Greater protrusive shear would be the result expected from the anatomy of the masticatory muscles, since the muscle mass capable of exerting a retractive pull on the mandible is much less than that which can exert a protrusive pull.…”
Section: Discussioncontrasting
confidence: 61%
“…Assuming that the working-side corpus and condyle in an anisognathic individual must translate mediolaterally and/or rotate about a vertical axis to bring the molars into functional occlusion, it is likely that, relative to more vertically oriented adductors, the balancing-side deep masseter is stretched beyond its resting length prior to the masticatory power stroke. This passive stretching of the sarcomeres beyond their resting length will result in reduced muscle-force production, as the amount of force a muscle can generate is inversely proportional to the distance it is stretched beyond its resting length (Carlson, 1977;Hylander, 1978Hylander, , 1992Weijs et al, 1989). Thus, given the increased relative activity of balancing-side deep masseter during mastication (Hylander et al, 1987(Hylander et al, , 1998(Hylander et al, , 2000Hylander and Johnson, 1994), and given a likely increase in the amount and duration of the transverse component of crushing force during the power stroke (Kay and Hiiemae, 1974;Hiiemae, 1978), isognathic jaws in anthropoids may enhance force generation in more transversely oriented balancing-side jaw muscles during the power stroke (vs. the primitive, more anisognathic masticatory apparatus of strepsirhines and, presumably, basal primates).…”
Section: Evolution Of Anthropoid Masticatory Adaptationsmentioning
confidence: 95%
“…The bite force was assumed to act at the center of the biting tooth (M 1 for molar biting and I 2 for incisal biting), and its direction was taken perpendicular to the occlusal plane. Although some studies showed that maximum bite force does not necessarily occur perpendicular to the occlusal plane, especially in the incisal region (Hylander, 1978;Baragar and Osborn, 1987;Koolstra et al, 1988), this assumption was made to render the system statically determinate (see below). Once their direction and point of application were established, the lever arms of the bite force and the muscle forces relative to the condyle were calculated by taking the perpendicular distance between the line of action of a given force and the condylar axis (Figs.…”
Section: Estimation Of Model Inputsmentioning
confidence: 99%